ESTUDO DOS EFEITOS DE ELEMENTOS DE LIGA NA SOLIDIFICAÇÃO DE UM FERRO FUNDIDO CINZENTO VIA ANÁLISE TÉRMICA - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2012)
The present study aimed at analyzing the effects of alloying elements on the solidification curves of a gray cast iron using the thermal analysis technique. Inoculation was performed by adding of only 0.02% (in wt. %) of IM22 inoculant, in order to minimize undercooling and provide a minimal quantity of nucleation sites for graphite during solidification. A constant inoculation condition allows highlighting the influence of alloying elements in the cooling curves, as well as in the solidification parameters. The following elements have been added to the base metal (in wt. %): selenium (0.2% to 0.5%), nickel (0.2% to 0.5%), iron-phosphorus (0.2% to 1.0%), silicon (0.05% to 0.4%), lead (0.2% to 1.0%) and tin (0.2% to 0.8%). The elementary powders were characterized by scanning electron microscopy (SEM) with energy-dispersive X-ray microanalysis (EDX). The base metal was produced in a medium frequency induction furnace and its chemical composition corresponded to a FC-25 class. The samples obtained after the addition of alloying elements were characterized by optical microscopy, optical emission spectrometry, tensile and hardness tests. The results showed that selenium has a strong effect on undercooling, favoring the formation of eutectic carbides. Nickel tends to favor the formation of type "A” graphite. The phosphorus has the effect of reducing the tensile strength of gray iron and promotes the formation of steadite, consisting of the eutectic of ferrite and iron phosphide (Fe3P). The silicon favors the formation of type "A" graphite. Lead has deleterious effect on the morphology of graphite. Tin has the effect of increasing the mechanical properties. The use of thermal analysis technique allowed the finding of good correlations between the different solidification parameters studied. The stable and metastable eutectic temperatures are strongly affected by the alloying elements. Finally, new equations for the temperatures of stable and metastable eutectics are proposed. The equations are based on experimental results and data extracted from ATAS program.
Keywords: ferro fundido cinzento; grafita; solidificação; análise térmica; elementos de liga; gray cast iron; graphite; solidification; thermal analysis; alloying elements; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA